Reframing residual sugars as value: A review on selective fermentation for ethanol and fructose co-production - Mohammed A. Zeinelabdeen; Adil A. Mohammed; Muzamul M. H. Siddig; Khalid M. O. Mohamad; Abubakr Hassan Kheiri (Konversi, 2026)
This review examines selective fermentation as an emerging strategy for the co-production of ethanol and fructose from mixed-sugar feedstocks. Conventional fermentation processes aim to maximize ethanol yield through complete sugar conversion, thereby treating residual sugars, particularly fructose as process inefficiencies. In contrast, selective fermentation exploits the intrinsic glucophilic behavior of Saccharomyces cerevisiae, enabling preferential conversion of glucose into ethanol while preserving fructose as a high-value co-product. Date-based substrates, including low-grade fruits and processing residues, are highlighted as abundant and underutilized resources rich in glucose–fructose mixtures. The review discusses the fundamental aspects of yeast metabolism, sugar transport mechanisms, and fermentation pathways that govern substrate selectivity. In addition, the role of fructose as a versatile platform molecule for the production of bio-based chemicals is emphasized within an integrated biorefinery framework. Key operational parameters affecting selective fermentation performance, such as temperature, pH, aeration, and substrate concentration, are critically analyzed. Existing studies reveal a persistent trade-off between ethanol yield and fructose retention, particularly under high-sugar and industrial-scale conditions. Furthermore, current limitations in kinetic modeling and process optimization are identified as major barriers to industrial implementation. Selective fermentation presents a promising approach to enhance process efficiency and economic value in biomass conversion systems. Future research should focus on developing robust kinetic models, optimizing operating conditions, and integrating downstream processing to enable scalable and economically viable ethanol–fructose biorefineries.